Bladder carcinoma presenting as Paget's disease of vulva: An uncommon entity - Anurag Mehta; Poojan Agarwal (Wolters Kluwer Medknow Publications, 2018)
Paget's disease of the vulva is a rare intraepithelial neoplasm, accounting for <5% of all vulvar lesions. The underlying mechanisms of this disease are still poorly understood, however, diagnosing a Pagetoid lesion early is of prime importance as it may forewarn an underlying systemic malignancy. We discuss the case of an elderly female who was being conservatively treated for infectious lesion of the lower urinary tract and vulva for months. She was subsequently confirmed on histopathology with vulvar Paget's and underlying urothelial carcinoma, with the help of an extensive panel of immunohistochemistry.